Magnetic nanocomposites based on phosphorus-containing polymers—structural characterization and thermal analysis. (14th February 2018) - Alosmanov, R M; Szuwarzyński, M; Schnelle-Kreis, J; Matuschek, G; Magerramov, A M; Azizov, A A; Zimmermann, R; Zapotoczny, S
Abstract: Fabrication of magnetic nanocomposites containing iron oxide nanoparticles formed in situ within a phosphorus-containing polymer matrix as well as its structural characterization and its thermal degradation is reported here. Comparative structural studies of the parent polymer and nanocomposites were performed using FTIR spectroscopy, x-ray diffraction, and atomic force microscopy. The results confirmed the presence of dispersed iron oxide magnetic nanoparticles in the polymer matrix. The formed composite combines the properties of porous polymer carriers and magnetic particles enabling easy separation and reapplication of such polymeric carriers used in, for example, catalysis or environmental remediation. Studies on thermal degradation of the composites revealed that the process proceeds in three stages while a significant influence of the embedded magnetic particles on that process was observed in the first two stages. Magnetic force microscopy studies revealed that nanocomposites and its calcinated form have strong magnetic properties. The obtained results provide a comprehensive characterization of magnetic nanocomposites and the products of their calcination that are important for their possible applications as sorbents (regeneration conditions, processing temperature, disposal, etc).